Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1002/1097-0142(19930201)71:3<745::aid-cncr2820710316>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Pernicious anemia and subsequent cancer. A population-based cohort study

Abstract: Background. Elevated risk of cancers of the stomach, colon, and buccal cavity, as well as of lymphoma and leukemia, have been reported for patients with pernicious anemia in case reports and hospital‐based and cross‐sectional studies. Methods. A cohort of 2021 men and 2496 women living in the Uppsala health care region in Sweden, discharged with a hospital diagnosis of pernicious anemia from 1965 to 1983, was followed for 20 years for subsequent risk of cancer. Results. A total of 553 cancers were diagnosed am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
159
2
10

Year Published

1996
1996
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 281 publications
(186 citation statements)
references
References 22 publications
(1 reference statement)
11
159
2
10
Order By: Relevance
“…In this cohort study of patients with PA we found a two-fold increase in the risk for stomach cancer in accordance with previous estimates (Blackburn et al, 1968;Brinton et al, 1989;Hsing et al, 1993). Our finding of an excess of cancer of the buccal cavity and pharynx is consistent with findings in the two large US and Swedish studies (Brinton et al, 1989;Hsing et al, 1993).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this cohort study of patients with PA we found a two-fold increase in the risk for stomach cancer in accordance with previous estimates (Blackburn et al, 1968;Brinton et al, 1989;Hsing et al, 1993). Our finding of an excess of cancer of the buccal cavity and pharynx is consistent with findings in the two large US and Swedish studies (Brinton et al, 1989;Hsing et al, 1993).…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of an excess of cancer of the buccal cavity and pharynx is consistent with findings in the two large US and Swedish studies (Brinton et al, 1989;Hsing et al, 1993). We have no information on important risk factors such as alcohol intake and smoking habits but two cases of buccal cavity and pharynx cancer had mention of alcoholism in the hospital record.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations